PEMERIKSAAN KESEHATAN GRATIS DAN PENYULUHAN TENTANG CARA PENGELOLAAN OBAT YANG BAIK SECARA MANDIRI PADA TEMAN TULI KOTA MAKASSAR - Santi, Elvira; Asjur, Asti Vebriyanti; Hasmar, Wahyu Nuraini; Musdar, Tamzil Azizi; Saputro, Syaifullah; Virlayani, Asnita; Ramadani, Ananda; Suhartini, Suhartini (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Hearing loss or deafness is one of the serious problems that occur throughout the country. Hearing loss is the loss of the ability to hear sounds or sounds in the normal frequency range to be heard. One of the reasons is the use of drugs. Due to physical, cognitive, and knowledge limitations, there are some deaf friends who, if they check their health at one of the health facilities (Public Health Center), are hindered by communication with health workers, which can cause many deaf friends to be unable to manage drugs properly independently. This study aims to provide free medical examinations and improve the understanding of deaf friends in managing drugs independently through these counseling activities. The method used is an interactive lecture and question and answer discussion using JBI (Sign Language Interpreter) involving about 62 deaf participants at Rahmatul Ilham mosque (Makassar City Hall mosque) Makassar City. The results showed an increase in understanding of participants in the indication or usefulness of the drug, storage, and drug side effects that will occur even though there is a small possibility of side effects. In conclusion, free medical check-ups and health counseling have proven effective in raising deaf friends ' awareness of the importance of correct medication management.